Optimizing diode laser performance: effective noise reduction in a three-dimension printing machine - Farhan, Mohammed F.; Salman, Suhad D.; Leman, Z.; Alkbir, M.F.M.; Januddi, Fatihhi (Mustansiriyah University College of Engineering, 2024)
This research focuses on reducing noise in 3D laser printers, commonly used in businesses and home offices. By fine-tuning printer components and analyzing noise levels, the primary goal is to minimize the noise produced by a 3D laser printer. The study involves modifying various printer parts and using a Raspberry Pi 4 as an AI control system. Noise reduction is tested by adjusting the speed and acceleration of the machine while maintaining precision. A sound level meter and analysis program are employed to measure and analyze the noise levels. Results indicate that altering components, such as stepper motor drivers, significantly reduces noise. Findings suggest that further noise reduction can be achieved through additional component tuning and noise insulation strategies. This approach improves the user experience by providing a quieter operation and enhances the overall performance and efficiency of 3D laser printers. By focusing on minimizing noise, this research provides practical solutions for creating quieter and more efficient 3D laser printers, benefiting both businesses and home offices. Insights from this study can be applied to develop advanced 3d laser printers with optimized noise levels.